Wood quality for kraft pulping of Eucalyptus globulus origins planted in Uruguay - Resquin, Fernando; Barrichelo, Luiz Ernesto George; Da Silva Jr., Francides Gomes; Brito, José Otávio; Sansigolo, Cláudio Angeli (My University, 2006)
Eucalyptus globulus is an important raw-material for kraft pulping and has a wide geographical distribution. The objective of this paper was to evaluate E. globulus origins in terms of their wood and pulp properties. The results showed that wood density values for the origins are within the values considered advisable for kraft pulp production; origins with the highest wood density were from the south of Victoria state; fiber dimensions indexes obtained in this study allow us to infer that all origins are suitable for paper production; holocellulose content varied from 69 to 72%; the highest screened yield values correspond to the origins from south Victoria.
Keywords: Basic density; Chemical composition; Eucalyptus globulus; Fiber dimensions; Kraft pulp; Pulp; Pulp strength; Refining; Wood quality